Patterns of dietary niche breadth and overlap are maintained for two closely related carnivores across broad geographic scales - Gobin, Jenilee; Szumski, Christa M.; Roth, James D.; Murray, Dennis L. (Frontiers in Ecology and Evolution, 2022)
Ecological studies investigating niche breadth and overlap often have limited spatial and temporal scale, preventing generalizations across varying environments and communities. For example, it is not clear whether species having restricted diets maintain such patterns relative to closely related species and across their geographic range of co-occurrence. We used stable isotope analysis of hair and fur samples collected from four regions of sympatry for Canada lynx (Lynx canadensis) and bobcat (Lynx rufus) spanning southern Canada and the northern United States, to test the prediction that the more generalist species (bobcat) exhibits a wider dietary niche than the more specialist species (Canada lynx) and that this pattern is consistent across different regions. We further predicted that Canada lynx diet would consistently exhibit greater overlap with that of bobcat compared to overlap of bobcat diet with Canada lynx. We found that Canada lynx had a narrower dietary niche than bobcat, with a high probability of overlap (85-95%) with bobcat, whereas the bobcat dietary niche had up to a 50% probability of overlap with Canada lynx. These patterns of dietary niche breadth and overlap were consistent across geographic regions despite some regional variation in diet breadth and position, for both species. Such consistent patterns could reflect a lack of plasticity in species dietary niches. Given the increasingly recognized importance of understanding dietary niche breadth and overlap across large spatial scales, further research is needed to investigate the mechanisms by which broad-scale patterns are maintained across species and systems.